Distribución temporal de aves rapaces diurnas en la Reserva “Playón de Mismaloya”, Jalisco, México - Hernández Vázquez, Salvador; Durand Martínez, Braulio Cesar; Esparza Salas, Rodrigo; Valadez González, Carmen (Revista de Biología Tropical, 2000)
Diurnal raptors were counted monthly in the “Playón de Mismaloya”, reserve, Jalisco, Mexico, from November 1997 to October 1998. We identified 11 species; eight of them migrants, one resident and two resident with migrant populations. The highest increase in total number of individuals was from December to March, influenced mainly by the presence of Caracara plancus (Crested Caracara), Falco sparverius (American Kestrel) and Pandion haliaetus (Osprey). The two former species were observed frequently in open areas, where they could detect prey more easily, while ospreys were found only in estuaries, lagoons and beach, where food was available.